RANCANG BANGUN SISTEM PERPUSTAKAAN ONLINE MENGGUNAKAN METODE MODEL VIEW CONTROLLER (MVC) PADA SMP NEGERI 1 REMBANG - Teguh Pradana (SPIRIT, 2020)
Abstract: SMP Negeri 1 Rembang Pasuruan regency is one of the public schools located in Pasuruan regency. The library provided by the school is a means of supporting and supporting the process of teaching and learning activities for students. With the increase of library functions maximally, expected to provide maximum education for the students. This step is one that is applied to improve the function of the library itself, the data processing system fast and precise. Information systems data processing books in the library needed by the school will be used for searching books, processing, storage, look back and also to channel the information itself. With the make system that will be built then I hope to improve the function of libraries and facilitate the operation, because the computerized system will be more strongly support students in finding the book they want. With this, it is expected to create a more optimal system with Model View Controller (MVC) method to increase students' reading interest in SMP Negeri 1 Rembang. Keywords: Library, Model View Controller (MVC), and Information Systems